FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE - Hotman Fredy; Sofyan Bantasyam; Kusmiyati Kusmiyati (Unversitas Prof. Dr. Moestopo (Beragama), 2021)
The purpose of this study is to obtain empirical evidence about the effects of leverage, firm size, return on assets, and executive characteristics of on tax avoidance of the manufacturing consumer goods industry sector companies listed on the Indonesia Stock Exchange from 2012-2015. Tax avoidance is a dependent variable, while leverage, firm size, return on assets, and executive characteristics are independent variables. The sample of this study is consist of 20 manufacturing companies that have been selected based on the criteria of the sample (purposive sampling) which is listed in Indonesia Stock Exchange (IDX) during the period 2012-2015 and used secondary data from audited financial statements. Hypotheses were tested using multiple regression analysis. Data were analyzed using SPSS software 21 version. The result of this study showed that leverage, and executive characteristics have no significant effects on tax avoidance, while firm size and return on assets have significant effects on tax avoidance.